Eksistensi Kitab Rohmatul Ummah Fi Ikhtilafil A’immah Sebagai Rujukan Pembelajaran Bab Nikah Di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: The Existence of the Rohmatul Ummah Fi Ikhtilafil A'immah Book as a Learning Reference for the Chapter of Marriage at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Nur Baiti; Tiara Novitasari; Dio Prabowo; Rifda Alfi Lutifasari (Litera Academica Publishing, 2026)
This study investigates the role of Rohmatul Ummah fi Ikhtilafil A’immah by Sadruddin Abu Abdillah Muhammad bin Abdurrahman al-Dimasyqi al- Khatib al-Utsmani as a primary reference in teaching the chapter of marriage (bab nikah) at Pondok Pesantren Raudlatul Muhibbin Al- Mustainiyyah, Surakarta. The text is a work of comparative fiqh that systematically, succinctly, and objectively maps the divergences of legal opinion among the four major Sunni schools: Hanafi, Maliki, Shafi’i, and Hanbali. Using a qualitative descriptive approach, this research explores the pedagogical application of the book, its relevance within the pesantren fiqh curriculum, and its influence on students’ legal reasoning. Data were obtained through interviews, classroom observation, and document analysis, and processed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The findings demonstrate that Rohmatul Ummah remains highly significant in fiqh education, fostering awareness of khilafiyah, promoting tolerance toward plural legal views, and facilitating the integration of classical jurisprudence with Indonesian positive law, notably the Compilation of Islamic Law (KHI) and Law No. 1 of 1974 on Marriage. Consequently, the book contributes to forming students with moderate, rational, and context- sensitive understandings of Islamic law.